Legal issues of the sale, perpetual usufruct and lease of agricultural real estate belonging to municipal resources - Suchoń, Aneta (Przegląd Prawa Rolnego, 2021)
The aim of the study was to solve selected legal issues connected with the sale, perpetual usufruct and lease of agricultural real estate from municipal resources. The considerations involved in the first place tenders organised by municipalities for the sale and lease of agricultural real estate, the municipality's pre-emptive right, the transformation of the right of perpetual usufruct of agricultural real estate into ownership, and spatial development plans adopted by municipalities. The conclusion of the considerations is, inter alia, that the Act on the management of real estate does not provide for separate regulations that would take into account the specificity of agricultural land. As for de lege ferenda conclusions, it is proposed that reference be made to the solutions contained in the Act on the management of agricultural real estate of the State Treasury with regard to tenders organised for the sale of land and the tenants’ pre-emptive right of purchase of agricultural real estate without a tender. Moreover, it is stressed that there should be a wider consideration of the agricultural aspect in the process of adopting and amending spatial development plans.